The Influence of Burnout, Eustress/Distress and Employee Wellbeing on Employee Performance - Hakim, Zainal; Maharani, Anita; Pintor Siolemba Patiro, Shine (Quantitative Economics and Management Studies, 2025)
This study aims to analyze the effect of burnout, eustress/distress, and employee wellbeing on employee performance . The study used quantitative methods with data collection through surveys of permanent employees who worked before and during the pandemic. The research sample was taken using simple random sampling technique with a minimum number of 50 respondents. Data collection was carried out through an online questionnaire, and data analysis was carried out using descriptive statistics with presentation in tabular form, mean, and standard deviation. The results showed that burnout has a significant negative effect on employee performance, while eustress has a significant positive effect. Employee wellbeing was also shown to have a positive effect on employee performance, indicating that employees who feel emotionally and psychologically wellbeing tend to perform better. The conclusion of this study is that companies should pay attention to employees' burnout and wellbeing conditions to maximize their performance, especially in facing post-pandemic challenges in the New Normal era. These findings can be the basis for company management to develop strategies to improve wellbeing and manage stress in the work environment so that employee performance remains optimal.